INTERNET OF THINGS (IoT) IN HEALTH INDUSTRY - Binti Wan Masri, Wan Nur Salwani (Journal of Computing Technologies and Creative Content, 2019)
Abstract— In the digital age, IoT has become a part of our daily activity, which is linked with machines, people, time, locations, and required a network, which fully integrated into what is known as IoT (Internet of Things). The Internet of things has become the most significant technology that connected people and technology [3]. The goal of the IoT in healthcare is to monitor patient safety by using technology, it to avoid the critical quality of life by using intelligent IoT environments. The protection of data with IoT is highly complex and hard because IoT is the main issues of worldwide connectivity and availability. Design security and privacy must be part of any case, project, or installation of IoT use. Several articles have worked with various technology and energy efficiency on the access control system. Few reports suggested multiple kinds of authentication protocols. A scheme is needed to fuse the authentication protocol with the mechanism of effective access control and to counter other assaults on patient safety and privacy information. Following the methodology for the contract of authentication, access control, and the mechanism for energy- efficient access control, it is suggested to adopt mixed methods to balance the gap.